The relationship of organizational culture and leadership in the context of SBE organizations - Peter Maier (Journal of Applied Leadership and Management, 2014)
Research questions: Main and first research question is to get a deeper insight into the relationship between the organizational culture (represented by the 4 main culture characteristics hierarchy, market, clan, and adhocracy), the leadership culture and "the outcome" of both towards the main organizational goal of all companies, to reach a real sustainable capability in organizational learning. Methods: Four empirical studies across different organizations using Quinn's Organizational Culture Assessment Inventory OCAI (Cameron & Quinn, 2011) to measure Organizational Culture and, independent from the leadership skills and traits itself, the "outcome" of the applied leadership culture using the "Leadership Productivity Model" LPM (Desjardins, 2012). Results: Although no direct linear correlation could be substantiated between the OCAI organizational culture profiles and the LPS leadership dimensions according to the leadership productivity model in the first step, yet the main elements of the suggested measurements (LPS, OCAI) create genuine value added in assessing and understanding an organization as an integral whole.
Keywords: 650